High-thermal-conductivity refractory castable and preparation method thereof
By using materials such as high thermal conductivity silicon carbide and modified graphite fibers in high thermal conductivity castables, the problem of low thermal conductivity of traditional high thermal conductivity materials is solved, significantly improving the thermal conductivity and mechanical properties of the materials, and prolonging the use of blast furnaces life.
Patent Information
- Application Number
- CN202411608011.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-12
AI Technical Summary
When traditional high-thermal conductivity materials fill the high-thermal conductivity parts of blast furnaces, due to the low thermal conductivity coefficient of the raw materials and the limited construction methods, there are many pores in the filled materials, which reduces the thermal conductivity and affects the service life of the blast furnace.
Using high thermal conductivity silicon carbide as the main component, combined with auxiliary components such as white corundum, pure calcium aluminate cement and modified graphite fibers, high thermal conductivity refractory castables are prepared through reasonable proportions, and the preparation method of modified graphite fibers is improved. Dispersibility and density of graphite fibers.
It significantly improves the thermal conductivity, mechanical properties and high-temperature dimensional stability of high-thermal conductivity refractory castables, and is suitable for filling and repairing of high-thermal conductivity parts, extending the service life of the blast furnace.
Smart Images

Figure BDA0005130150190000041 
Figure BDA0005130150190000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a high thermal conductivity refractory castable and a preparation method thereof. Background Art
[0002] Refractory castable is an important amorphous refractory material, which is a mixture of refractory aggregate, powder, binder and admixture, and is mixed with water or liquid binder to form a mud material that can be constructed by pouring method. It has the advantages of simple production process, convenient construction and long service life. It is widely used in lining materials of various high-temperature industrial furnaces such as high thermal shock, strong mechanical impact and high temperature stability. The gaps between the carbon bricks at the bottom of the blast furnace and the bottom sealing plate, and between the carbon bricks of the furnace and the cooling wall need to be filled with high thermal conductivity materials. The repair of damaged parts of carbon bricks during overhaul of the blast furnace also needs to use high thermal conductivity materials. The traditional construction method is to fill the carbon ramming mass (high thermal conductivity material) in the high thermal conductivity part by ramming. Due to the low thermal conductivity of the raw material of the carbon ramming mass and the limitation of the ramming method during construction, there are many pores in the high thermal conductivity material after filling, which greatly reduces the thermal conductivity of the material itself, thereby affecting the service life of the blast furnace.
[0003] Chinese patent application with application number CN202010512525.9 discloses a silicon nitride composite high thermal conductivity castable, which is prepared in proportion from raw materials such as fused corundum, kyanite, silicon carbide, silicon nitride, silicon powder, activated alumina powder, spherical asphalt, carbon black powder, carbon resin powder, carbon dispersant, antioxidant, organic fiber, and explosion-proof agent. During construction, a binder silica sol or pure calcium aluminate cement is added. The carbon element and carbon dispersant improve the thermal conductivity and slag resistance of the material; Chinese patent application with application number CN202110286791.9 discloses a high thermal conductivity and wear-resistant castable prepared from secondary silicon-molybdenum bricks. The particle size and mass percentage of each raw material are as follows: 40-50% of secondary silica-molybdenum bricks with a particle size of ≤6mm, 20-30% of silicon carbide with a particle size of ≤6mm, 1-10% of silicon micropowder, 2-10% of calcium aluminate cement, 2-20% of coke gemstone micropowder with a particle size of 5μm, and also include 0.02-0.5% of the mass percentage of all the above ingredients as admixtures, thereby realizing the utilization of discarded silica-molybdenum brick resources to prepare cost-effective high thermal conductivity and wear-resistant materials; the above patents all improve the thermal conductivity of the castable by adding high thermal conductivity raw materials, but the thermal conductivity of the castable obtained still cannot meet the use requirements, and there is a large room for improvement. Summary of the invention
[0004] The purpose of the present invention is to provide a high thermal conductivity refractory castable and a preparation method thereof in view of the deficiencies in the prior art. The high thermal conductivity refractory castable is mainly composed of high thermal conductivity silicon carbide, and white corundum, pure calcium aluminate cement, modified graphite fiber, silicon powder and the like are auxiliary components. Through reasonable proportioning, the prepared high thermal conductivity refractory castable has good thermal conductivity, mechanical properties and high temperature dimensional stability, and is suitable for filling and repairing high thermal conductivity parts.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0006] A high thermal conductivity refractory castable, comprising the following components in parts by weight: 50-60 parts of silicon carbide; 10-15 parts of white corundum; 5-8 parts of pure calcium aluminate cement; 3-5 parts of modified graphite fiber; 2-3 parts of silicon micropowder; 1-2 parts of a binder; and 0.3-0.5 parts of a water reducer.
[0007] Furthermore, the silicon carbide includes particles with a particle size of 1-3 mm, particles with a particle size of 0-1 mm, and fine powder with a particle size of 200 mesh in a mass ratio of 3-4:1-2:1.
[0008] Furthermore, the white corundum includes particles with a particle size of 1-3 mm, particles with a particle size of 0-1 mm, and fine powder with a particle size of 325 mesh in a mass ratio of 2-3:1-2:1.
[0009] Furthermore, the particle size of the silicon micropowder is 200-325 mesh; the binder is silica sol; and the water reducer is one or a mixture of sodium tripolyphosphate, sodium hexametaphosphate, and calcium lignin sulfonate.
[0010] In the technical solution of the present invention, the preparation method of the modified graphite fiber is:
[0011] S1. Add graphite fiber to ethanol aqueous solution, disperse evenly, add 3-aminopropyltriethoxysilane, adjust the pH value of the solution to 5-6, stir and react at 50-60° C. for 3-4 hours, filter after the reaction is completed, wash the filter residue with ethanol, and dry to obtain amino graphite fiber;
[0012] S2, adding amino graphite fiber to N,N-dimethylformamide, dispersing evenly, adding 2,2-dihydroxymethylpropionic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 70-80° C. for 4-5 hours, filtering after the reaction is completed, washing the filter residue with water and ethanol in turn, and drying to obtain polyhydroxy graphite fiber;
[0013] S3. Add polyhydroxy graphite fiber into ethanol and disperse it evenly. Add sodium chloride-long chain alkyl sulfonate and potassium hydroxide. Stir and react at 60-70°C for 3-4 hours. After the reaction is completed, filter and wash the filter residue with water and ethanol in turn. After drying, obtain modified graphite fiber.
[0014] Furthermore, in step S1, the mass ratio of the graphite fiber, 3-aminopropyltriethoxysilane and ethanol aqueous solution is 1:0.3-0.4:15-20.
[0015] Furthermore, in step S2, the mass ratio of the amino graphite fiber, 2,2-dihydroxymethylpropionic acid, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:0.2-0.25:0.1-0.15.
[0016] Furthermore, in step S3, the mass ratio of the polyhydroxy graphite fiber, sodium chloride-long chain alkyl sulfonate, and potassium hydroxide is 1:0.5-0.6:0.08-0.1.
[0017] In the technical scheme of the present invention, the preparation method of the sodium chloride-long-chain alkyl sulfonate is: toluene, sodium 4-hydroxybutyl sulfonate, 7-chloroheptanoic acid and p-toluenesulfonic acid are added to a reaction container, stirred evenly, heated to 110° C., refluxed for 4-5 hours, and the water generated by the reaction was collected by a water separator. After the reaction is completed, toluene is removed, water and dichloromethane are added for extraction, and the aqueous phase is concentrated under reduced pressure to obtain the sodium chloride-long-chain alkyl sulfonate.
[0018] Furthermore, the molar ratio of the sodium 4-hydroxybutyl sulfonate, 7-chloroheptanoic acid, and p-toluenesulfonic acid is 1:1.1-1.2:0.01-0.02.
[0019] The present invention also provides a method for preparing a high thermal conductivity refractory castable, comprising the following steps: mixing silicon carbide, white corundum, pure calcium aluminate cement, modified graphite fiber, silicon micropowder, a binder, and a water reducer uniformly according to a mass ratio to obtain a high thermal conductivity refractory castable.
[0020] The present invention has the following beneficial effects:
[0021] The invention uses high thermal conductivity graphite fiber as a raw material for modification, first reacts with 3-aminopropyltriethoxysilane, introduces amino groups on the surface of the graphite fiber, and under the action of condensation agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, utilizes amino groups and 2,2-dihydroxymethylpropionic acid for condensation, and the imino groups react with chlorinated-long-chain sodium alkyl sulfonate, and sequentially introduces polyhydroxy groups and long-chain sodium alkyl sulfonate groups into the surface of the graphite fiber to obtain modified graphite fiber; the invention adds the modified graphite fiber to the high thermal conductivity refractory castable In the present invention, the flexible long-chain sodium alkyl sulfonate groups grafted on the surface of the modified graphite fiber can improve the dispersion of the graphite fiber in the mixture and prevent its agglomeration. Together with silicon carbide, they give the castable high thermal conductivity, improve the brittleness of the graphite fiber, and improve the high-temperature dimensional stability of the castable. The polyhydroxy groups grafted on the surface of the modified graphite fiber can react with the silanol groups on the surface of the silica sol to promote the gelation of the silica sol and the formation of the silica sol network structure, which can improve the density of the castable and thus help to improve the comprehensive performance of the castable.
[0022] The high thermal conductivity refractory castable provided by the present invention has high thermal conductivity silicon carbide as the main component, and white corundum, pure calcium aluminate cement, modified graphite fiber, silicon micropowder and the like as auxiliary components. Through reasonable proportioning, the prepared high thermal conductivity refractory castable has good thermal conductivity, mechanical properties and high-temperature dimensional stability, and is suitable for filling and repairing high thermal conductivity parts. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In the technical scheme of the present invention, the chemical reagents used are all commercially available, among which 3-aminopropyltriethoxysilane CAS No. 919-30-2; 2,2-dihydroxymethylpropionic acid CAS No. 4767-03-7; 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride CAS No. 25952-53-8; potassium hydroxide CAS No. 1310-58-3; sodium 4-hydroxybutanesulfonate CAS No. 31465-25-5; 7-Chloroheptanoic acid CAS No. 821-57-8; p-toluenesulfonic acid CAS No. 104-15-4; toluene CAS No. 108-88-3; N,N-dimethylformamide CAS No. 68-12-2; dichloromethane CAS No. 75-09-2; ethanol CAS No. 64-17-5; the content of silicon dioxide in the silica sol is 40wt%; the diameter of the graphite fiber is 5μm and the length is 5-10mm, which is purchased from Hebei Jingxin Technology Co., Ltd.
[0025] In the technical solution of the present invention, the preparation method of sodium chloride-long-chain alkyl sulfonate is:
[0026] 550 mL of toluene, 20.0 g of sodium 4-hydroxybutyl sulfonate, 20.6 g of 7-chloroheptanoic acid and 0.4 g of p-toluenesulfonic acid were added to the reaction container, stirred evenly, heated to 110° C., refluxed for 5 h, and the water generated by the reaction was collected by a water separator. After the reaction was completed, toluene was removed, water and dichloromethane were added for extraction, and the aqueous phase was concentrated under reduced pressure to obtain 30.5 g of sodium chlorinated-long-chain alkyl sulfonate; wherein the molar ratio of sodium 4-hydroxybutyl sulfonate, 7-chloroheptanoic acid and p-toluenesulfonic acid was 1:1.1:0.02; the reaction process was:
[0027]
[0028] Sodium chloride-long chain alkyl sulfonate: ESI (m / z): 323.8 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 4.13 (t, J=7.2Hz, 2H), 3.25-3.32 (m, 4H), 2.32 (d, J=6 .8Hz, 2H), 1.77-1.82(m, 2H), 1.61-1.66(m, 4H), 1.49-1.55(m, 4H), 1.33-1.38(m, 2H).
[0029] Example 1
[0030] A high thermal conductivity refractory castable, comprising the following components by weight: 60 parts of silicon carbide; 13 parts of white corundum; 8 parts of pure calcium aluminate cement; 5 parts of modified graphite fiber; 3 parts of silicon micropowder; 2 parts of binder; and 0.4 parts of water reducing agent.
[0031] Silicon carbide includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 200 mesh in a mass ratio of 4:2:1; white corundum includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 325 mesh in a mass ratio of 3:2:1; the particle size of silicon micropowder is 325 mesh; the binder is silica sol; and the water reducer is sodium tripolyphosphate.
[0032] The preparation method of modified graphite fiber is:
[0033] S1. Add graphite fiber to ethanol aqueous solution, disperse evenly, add 3-aminopropyltriethoxysilane, adjust the pH value of the solution to 6, stir and react at 60° C. for 3 hours, filter after the reaction is completed, wash the filter residue with ethanol, and dry to obtain amino graphite fiber; wherein the mass ratio of graphite fiber, 3-aminopropyltriethoxysilane, and ethanol aqueous solution is 1:0.4:20;
[0034] S2, adding amino graphite fiber to N, N-dimethylformamide, dispersing evenly, adding 2,2-dihydroxymethylpropionic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 80°C for 5 hours, filtering after the reaction is completed, washing the filter residue with water and ethanol in turn, and drying to obtain polyhydroxy graphite fiber; wherein the mass ratio of amino graphite fiber, 2,2-dihydroxymethylpropionic acid, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:0.25:0.15;
[0035] S3. Add polyhydroxy graphite fibers into ethanol and disperse them evenly. Add sodium chloride-long-chain alkyl sulfonate and potassium hydroxide. Stir and react at 70°C for 4 hours. After the reaction is completed, filter and wash the residue with water and ethanol in turn. Dry and obtain modified graphite fibers. The mass ratio of polyhydroxy graphite fibers, sodium chloride-long-chain alkyl sulfonate and potassium hydroxide is 1:0.6:0.1.
[0036] A method for preparing a high thermal conductivity refractory castable comprises the following steps: mixing silicon carbide, white corundum, pure calcium aluminate cement, modified graphite fiber, silicon micropowder, a binder and a water reducing agent uniformly according to a mass ratio to obtain a high thermal conductivity refractory castable.
[0037] Example 2
[0038] A high thermal conductivity refractory castable, comprising the following components by weight: 55 parts of silicon carbide; 15 parts of white corundum; 6 parts of pure calcium aluminate cement; 4 parts of modified graphite fiber; 2 parts of silicon micropowder; 1.5 parts of a binder; and 0.5 parts of a water reducing agent.
[0039] Silicon carbide includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 200 mesh in a mass ratio of 3:1.5:1; white corundum includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 325 mesh in a mass ratio of 2.5:1.5:1; the particle size of silicon micropowder is 270 mesh; the binder is silica sol; and the water reducer is calcium lignin sulfonate.
[0040] The preparation method of modified graphite fiber is:
[0041] S1. Add graphite fiber to ethanol aqueous solution, disperse evenly, add 3-aminopropyltriethoxysilane, adjust the pH value of the solution to 5.5, stir and react at 50°C for 4 hours, filter after the reaction is completed, wash the filter residue with ethanol, and dry to obtain amino graphite fiber; wherein the mass ratio of graphite fiber, 3-aminopropyltriethoxysilane, and ethanol aqueous solution is 1:0.35:18;
[0042] S2, adding amino graphite fiber to N, N-dimethylformamide, dispersing evenly, adding 2,2-dihydroxymethylpropionic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 75°C for 4 hours, filtering after the reaction is completed, washing the filter residue with water and ethanol in turn, and drying to obtain polyhydroxy graphite fiber; wherein the mass ratio of amino graphite fiber, 2,2-dihydroxymethylpropionic acid, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:0.2:0.1;
[0043] S3. Add polyhydroxy graphite fibers into ethanol and disperse them evenly. Add sodium chloride-long-chain alkyl sulfonate and potassium hydroxide. Stir and react at 60°C for 3.5 hours. After the reaction is completed, filter and wash the residue with water and ethanol in turn. After drying, obtain modified graphite fibers; wherein the mass ratio of polyhydroxy graphite fibers, sodium chloride-long-chain alkyl sulfonate and potassium hydroxide is 1:0.55:0.09.
[0044] The preparation method of a high thermal conductivity refractory castable is the same as that in Example 1.
[0045] Example 3
[0046] A high thermal conductivity refractory castable, comprising the following components in parts by weight: 50 parts of silicon carbide; 10 parts of white corundum; 5 parts of pure calcium aluminate cement; 3 parts of modified graphite fiber; 2.5 parts of silicon micropowder; 1 part of binder; and 0.3 parts of water reducing agent.
[0047] Silicon carbide includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 200 mesh in a mass ratio of 3.5:1:1; white corundum includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 325 mesh in a mass ratio of 2:1:1; the particle size of silicon micropowder is 200 mesh; the binder is silica sol; and the water reducer is sodium hexametaphosphate.
[0048] The preparation method of modified graphite fiber is:
[0049] S1. Add graphite fiber to ethanol aqueous solution, disperse evenly, add 3-aminopropyltriethoxysilane, adjust the pH value of the solution to 5, stir and react at 55° C. for 3.5 hours, filter after the reaction is completed, wash the filter residue with ethanol, and dry to obtain amino graphite fiber; wherein the mass ratio of graphite fiber, 3-aminopropyltriethoxysilane, and ethanol aqueous solution is 1:0.3:15;
[0050] S2, adding amino graphite fiber to N, N-dimethylformamide, dispersing evenly, adding 2,2-dihydroxymethylpropionic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 70°C for 4.5 hours, filtering after the reaction is completed, washing the filter residue with water and ethanol in turn, and drying to obtain polyhydroxy graphite fiber; wherein the mass ratio of amino graphite fiber, 2,2-dihydroxymethylpropionic acid, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:0.23:0.13;
[0051] S3. Add polyhydroxy graphite fibers into ethanol and disperse them evenly. Add sodium chloride-long-chain alkyl sulfonate and potassium hydroxide. Stir and react at 65°C for 3 hours. After the reaction is completed, filter and wash the filter residue with water and ethanol in turn. After drying, obtain modified graphite fibers; wherein the mass ratio of polyhydroxy graphite fibers, sodium chloride-long-chain alkyl sulfonate and potassium hydroxide is 1:0.5:0.08.
[0052] The preparation method of a high thermal conductivity refractory castable is the same as that in Example 1.
[0053] Comparative Example 1
[0054] Compared with Example 1, the modified graphite fiber in the components of this comparative example is replaced by polyhydroxy graphite fiber.
[0055] A high thermal conductivity refractory castable, comprising the following components by weight: 60 parts of silicon carbide; 13 parts of white corundum; 8 parts of pure calcium aluminate cement; 5 parts of polyhydroxy graphite fiber; 3 parts of silicon micropowder; 2 parts of binder; and 0.4 parts of water reducing agent.
[0056] Silicon carbide includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 200 mesh in a mass ratio of 4:2:1; white corundum includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 325 mesh in a mass ratio of 3:2:1; the particle size of silicon micropowder is 325 mesh; the binder is silica sol; and the water reducer is sodium tripolyphosphate.
[0057] The preparation method of polyhydroxy graphite fiber is:
[0058] S1, the same as step S1 in Example 1;
[0059] S2. Same as step S1 in Example 1.
[0060] The preparation method of a high thermal conductivity refractory castable is the same as that in Example 1.
[0061] Comparative Example 2
[0062] Compared with Example 1, this comparative example replaces the modified graphite fiber in the components with amino graphite fiber.
[0063] A high thermal conductivity refractory castable, comprising the following components by weight: 60 parts of silicon carbide; 13 parts of white corundum; 8 parts of pure calcium aluminate cement; 5 parts of amino graphite fiber; 3 parts of silicon micropowder; 2 parts of binder; and 0.4 parts of water reducing agent.
[0064] Silicon carbide includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 200 mesh in a mass ratio of 4:2:1; white corundum includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 325 mesh in a mass ratio of 3:2:1; the particle size of silicon micropowder is 325 mesh; the binder is silica sol; and the water reducer is sodium tripolyphosphate.
[0065] The preparation method of amino graphite fiber is the same as step S1 of Example 1.
[0066] The preparation method of a high thermal conductivity refractory castable is the same as that in Example 1.
[0067] Comparative Example 3
[0068] Compared with Example 1, this comparative example replaces the modified graphite fiber in the components with graphite fiber.
[0069] A high thermal conductivity refractory castable, comprising the following components by weight: 60 parts of silicon carbide; 13 parts of white corundum; 8 parts of pure calcium aluminate cement; 5 parts of graphite fiber; 3 parts of silicon micropowder; 2 parts of binder; and 0.4 parts of water reducing agent.
[0070] Silicon carbide includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 200 mesh in a mass ratio of 4:2:1; white corundum includes particles with a particle size of 1-3mm, particles with a particle size of 0-1mm, and fine powder with a particle size of 325 mesh in a mass ratio of 3:2:1; the particle size of silicon micropowder is 325 mesh; the binder is silica sol; and the water reducer is sodium tripolyphosphate.
[0071] The preparation method of a high thermal conductivity refractory castable is the same as that in Example 1.
[0072] Performance Testing
[0073] 5% water by weight of the castable was added to the high thermal conductivity refractory castables prepared in Examples 1-3 and Comparative Examples 1-3, respectively, the mixture was mixed evenly, vibrated and molded, and demolded after curing at room temperature for 24 hours. The bulk density, flexural strength, compressive strength, linear change rate and thermal conductivity of the samples were tested, wherein the bulk density was referred to the YB / T 5200-1993 standard; the flexural strength was referred to the GB / T3002-2017 standard; the compressive strength was referred to the GB / T 34218-2017 standard; the linear change rate was referred to the GB / T5988-2007 standard; the results are shown in Table 1 below.
[0074] Table 1 Performance test results
[0075]
[0076] It can be seen from the results in Table 1 that the high thermal conductivity refractory castables prepared in Examples 1-3 of the present invention have good thermal conductivity, mechanical properties and high temperature dimensional stability. Compared with Comparative Examples 1-3, the surface of the modified graphite fiber added in Example 1 of the present invention is grafted with long-chain sodium alkyl sulfonate groups and polyhydroxy groups, wherein the flexible long-chain sodium alkyl sulfonate groups can improve the brittleness of the graphite fiber, improve the high temperature dimensional stability of the castable, and can also improve the dispersibility of the graphite fiber in the mixture, and together with silicon carbide, improve the thermal conductivity of the castable; the polyhydroxy groups can react with the silanol groups on the surface of the silica sol to promote the gelation of the silica sol and the formation of the silica sol network structure, which can improve the density of the castable, and thus help to improve the comprehensive performance of the castable.
[0077] It should be noted that, in this document, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device; although the embodiments of the present application have been shown and described, it can be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A high thermal conductivity refractory castable, characterized in that: The invention comprises the following components by weight: 50-60 parts of silicon carbide; 10-15 parts of white corundum; 5-8 parts of pure calcium aluminate cement; 3-5 parts of modified graphite fiber; 2-3 parts of silicon micropowder; 1-2 parts of binder; 0.3-0.5 parts of water reducing agent; The preparation method of the modified graphite fiber is: S1. Add graphite fiber to ethanol aqueous solution, disperse evenly, add 3-aminopropyltriethoxysilane, adjust the pH value of the solution to 5-6, stir and react at 50-60° C. for 3-4 hours, filter after the reaction is completed, wash the filter residue with ethanol, and dry to obtain amino graphite fiber; S2, adding amino graphite fiber to N,N-dimethylformamide, dispersing evenly, adding 2,2-dihydroxymethylpropionic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirring and reacting at 70-80° C. for 4-5 hours, filtering after the reaction is completed, washing the filter residue with water and ethanol in turn, and drying to obtain polyhydroxy graphite fiber; S3. Add polyhydroxy graphite fiber into ethanol and disperse it evenly. Add sodium chloride-long chain alkyl sulfonate and potassium hydroxide. Stir and react at 60-70°C for 3-4 hours. After the reaction is completed, filter and wash the filter residue with water and ethanol in turn. After drying, obtain modified graphite fiber.
2. A high thermal conductivity refractory castable according to claim 1, characterized in that: The preparation method of the sodium chloride-long-chain alkyl sulfonate described in step S3 is: toluene, sodium 4-hydroxybutyl sulfonate, 7-chloroheptanoic acid and p-toluenesulfonic acid are added to a reaction container, stirred evenly, heated to 110° C., refluxed for 4-5 hours, and the water generated by the reaction was collected by a water separator. After the reaction is completed, toluene is removed, water and dichloromethane are added for extraction, and the aqueous phase is concentrated under reduced pressure to obtain the sodium chloride-long-chain alkyl sulfonate.
3. A high thermal conductivity refractory castable according to claim 2, characterized in that: The molar ratio of the sodium 4-hydroxybutyl sulfonate, 7-chloroheptanoic acid and p-toluenesulfonic acid is 1:1.1-1.2:0.01-0.
02.
4. A high thermal conductivity refractory castable according to claim 1, characterized in that: The mass ratio of the graphite fiber, 3-aminopropyltriethoxysilane and ethanol aqueous solution in step S1 is 1:0.3-0.4:15-20.
5. A high thermal conductivity refractory castable according to claim 1, characterized in that: The mass ratio of the amino graphite fiber, 2,2-dihydroxymethylpropionic acid, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride in step S2 is 1:0.2-0.25:0.1-0.
15.
6. A high thermal conductivity refractory castable according to claim 1, characterized in that: The mass ratio of the polyhydroxy graphite fiber, sodium chloride-long chain alkyl sulfonate and potassium hydroxide in step S3 is 1:0.5-0.6:0.08-0.
1.
7. A high thermal conductivity refractory castable according to claim 1, characterized in that: The silicon carbide includes particles with a particle size of 1-3 mm, particles with a particle size of 0-1 mm, and fine powder with a particle size of 200 meshes at a mass ratio of 3-4:1-2:
1.
8. A high thermal conductivity refractory castable according to claim 1, characterized in that: The white corundum includes particles with a particle size of 1-3 mm, particles with a particle size of 0-1 mm, and fine powder with a particle size of 325 mesh in a mass ratio of 2-3:1-2:
1.
9. A high thermal conductivity refractory castable according to claim 1, characterized in that: The particle size of the silicon micropowder is 200-325 meshes; the binder is silica sol; the water reducer is one or a mixture of sodium tripolyphosphate, sodium hexametaphosphate, and calcium lignin sulfonate.
10. A method for preparing a high thermal conductivity refractory castable according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: silicon carbide, white corundum, pure calcium aluminate cement, modified graphite fiber, silicon micropowder, a binder and a water reducing agent are uniformly mixed according to the mass ratio to obtain a high thermal conductivity refractory castable.
Citation Information
Patent Citations
Reverse-direction tape translation
CA919302A
Silicon nitride composite high-thermal-conductivity castable
CN111517815A
A high thermal conductivity and wear-resistant castable prepared from secondary silica-mullite bricks
CN113045322B
Castable for blast-furnace tapping channel and preparation method thereof
CN103664211A
Tundish coating material and preparation method thereof
CN117585987A